Use of a control film piece in radiochromic film dosimetry. Issue 1 (January 2016) - Aldelaijan, Saad; Alzorkany, Faisal; Moftah, Belal; Buzurovic, Ivan; Seuntjens, Jan; Tomic, Nada; Devic, Slobodan
Highlights: Impact of environmental conditions on radiochromic film response is addressed. Use of a control radiochromic film piece improves the accuracy of measured dose. Gain in accuracy is a trade-off in uncertainty loss. Three levels of action dependent on signal detected by the control film piece. Abstract: Purpose: Radiochromic films change their color upon irradiation due to polymerization of the sensitive component embedded within the sensitive layer. However, agents, other than monitored radiation, can lead to a change in the color of the sensitive layer (temperature, humidity, UV light) that can be considered as a background signal and can be removed from the actual measurement by using a control film piece. In this work, we investigate the impact of the use of control film pieces on both accuracy and uncertainty of dose measured using radiochromic film based reference dosimetry protocol. Methods: We irradiated "control" film pieces (EBT3 GafChromic TM film model) to known doses in a range of 0.05–1 Gy, and five film pieces of the same size to 2, 5, 10, 15 and 20 Gy, considered to be "unknown" doses. Depending on a dose range, two approaches to incorporating control film piece were investigated: signal and dose corrected method. Results: For dose values greater than 10 Gy, the increase in accuracy of 3% led to uncertainty loss of 5% by using dose corrected approach. At lower doses and signals of the order of 5%, we observed an increase in accuracy of 10% with a loss of uncertainty lower than 1% by using the corrected signal approach. Conclusions: Incorporation of the signal registered by the control film piece into dose measurement analysis should be a judgment call of the user based on a tradeoff between deemed accuracy and acceptable uncertainty for a given dose measurement.